Clinical, genetic and immunological characteristics of 40 Chinese patients with CD40 ligand deficiency. (21st July 2019) - Du, Xiao; Tang, Wenjing; Chen, Xuemei; Zeng, Ting; Wang, Yanping; Chen, Zhi; Xu, Tao; Zhou, Lina; Tang, Xuemei; An, Yunfei; Zhao, Xiaodong
Abstract: CD40 ligand (CD40L) deficiency is a rare but life‐threatening primary immunodeficiency caused by mutations in the CD40L gene. Here, we investigated a cohort of 40 genetically diagnosed CD40L‐deficient patients from the Chinese mainland, analysed their clinical and genetic data, and examined CD40L expression, the proportion of T cell subsets, B cell subsets and T follicular helper (Tfh) cells. The aim was to provide a complete picture of CD40L deficiency. Initial presentations of the patient cohort mainly involved recurrent fever (47.5%) and sinopulmonary infection (42.5%). Life‐threatening infections (42.5%), caused by various pathogens, were the most serious threats faced by CD40L‐deficient patients, while neutropenia (57.5%) remained the most common complication. Opportunistic infections, including Pneumocystis carinii pneumonia and invasive fungal disease associated with Talaromyces marneffei, were also common in the cohort. In addition, seven patients (17.5%) suffered BCGitis/BCGosis, which is a major problem facing a planned immunization programme in China. It was intriguing that reduced IgM levels were observed in 12.5% of patients, while normal or elevated IgA levels were shown in 47.5% of patients. Thirty‐seven unique mutations were identified in 40 patients; of these, 10 were novel. Furthermore, we observed a lower percentage of NK cells, Tfh cells, and central memory CD4 + T cells, and an extremely small class‐switched memory B cell population, in CD40L‐deficient patients. Patients who underwent hematopoietic stem cell transplantation experienced better disease remission. Taken together, our data establish the largest database about CD40L deficiency in China and provide genetic, immunologic and clinical information about Chinese CD40L‐deficient patients.